David Livingstone : missionary and explorer - Wellman, Sam. (Uhrichsville : Barbour books, 1995)
Discusses the explorer's formative years in Scotland, training as a missionary, expeditions to Africa, and many discoveries there.
Includes bibliographical references (p. 205-206) and index.
Keywords: Livingstone, David, -- 1813-1873 -- Juvenile literature; Livingstone, David, -- 1813-1873.; Explorers -- Africa, Southern -- Biography -- Juvenile literature; Explorers -- Scotland -- Biography -- Juvenile literature; Missionaries, Medical -- Africa, Southern -- Biography -- Juvenile literature; Explorers; Missionaries